Prospects for us Digital Diplomacy in Central Asia (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
Given the current trends in the region, such as the rise of the Internet and social media, the increasing influence of bloggers in decision-making, and the increasing activity of human rights activists, it is possible to highlight the prospects for US digital diplomacy to become more active in these areas in the near future. In particular, in recent years, the US government has paid increased attention to the human rights reports and country rankings of reputable international rating and index organizations and international non-governmental non-profit organizations.